Endothelial Sirtuin 3 Dictates Glucose Transport to Cardiomyocyte and Sensitizes Pressure Overload‐Induced Heart Failure. Issue 11 (2nd June 2020) - Zeng, Heng; He, Xiaochen; Chen, Jian‐Xiong
Abstract : Background: Alterations of energetic metabolism are suggested to be an important contributor to pressure overload (PO)‐induced heart failure. Our previous study reveals that knockout of endothelial Sirtuin 3 (SIRT3) alters glycolysis and impairs diastolic function. We hypothesize that endothelial SIRT3 regulates glucose utilization of cardiomyocytes and sensitizes PO‐induced heart failure. Methods and Results: SIRT3 endothelial cell knockout mice and their control SIRT3 LoxP mice were subjected to PO by transverse aortic constriction for 7 weeks. The ratio of heart weight to tibia length was increased in both strains of mice, in which SIRT3 endothelial cell knockout mice+transverse aortic constriction exhibited more severe cardiac hypertrophy. Coronary blood flow and systolic function were significantly decreased in SIRT3 endothelial cell knockout mice+transverse aortic constriction compared with SIRT3 LoxP mice+transverse aortic constriction, as evidenced by lower systolic/diastolic ratio, ejection fraction, and fractional shortening. PO‐induced upregulation of apelin and glucose transporter 4 were significantly reduced in the hearts of SIRT3 endothelial cell knockout mice. In vitro, levels of hypoxia‐inducible factor‐1α and glucose transporter 1 and glucose uptake were significantly reduced in SIRT3 knockout endothelial cells. Furthermore, hypoxia‐induced apelin expression was abolished together with reduced apelin‐mediated glucose uptake in SIRT3 knockout endothelial cells. Exposure of cardiomyocyte with apelin increased expression of glucose transporter 1 and glucose transporter 4. This was accompanied by a significant increase in glycolysis. Supplement of apelin in SIRT3 knockout hypoxic endothelial cell media increased glycolysis in the cardiomyocytes. Conclusions: Knockout of SIRT3 disrupts glucose transport from endothelial cells to cardiomyocytes, reduces cardiomyocyte glucose utilization via apelin in a paracrine manner, and sensitizes PO‐induced heart failure. Endothelial SIRT3 may regulate cardiomyocyte glucose availability and govern the function of the heart.